1990
DOI: 10.1086/646148
|View full text |Cite
|
Sign up to set email alerts
|

Increasing ICU Staff Handwashing: Effects of Education and Group Feedback

Abstract: This study provides an evaluation of the effectiveness of methods to increase handwashing (HW) by nurses working in an intensive care unit. After baseline observations, two interventions were implemented in sequence: three series of classes conducted by the infection control nurse (ICN); and feedback to staff about handwashing errors on the previous day. Staff were aware that handwashing was being observed throughout the study. The educational intervention produced an immediate increase in HW that was followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1
6

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(140 citation statements)
references
References 7 publications
4
129
1
6
Order By: Relevance
“…Another finding was that some HCWs believed that they washed their hands when necessary, even when observations indicated that they did not. 24 Finally, some HCWs argued that the lack of scientific information of the definitive impact of improved hand hygiene on nosocomial infections rates decreases their motivation to comply with recommendations.…”
Section: Compliance W I T H H a N D H Y G I E N Ementioning
confidence: 99%
See 1 more Smart Citation
“…Another finding was that some HCWs believed that they washed their hands when necessary, even when observations indicated that they did not. 24 Finally, some HCWs argued that the lack of scientific information of the definitive impact of improved hand hygiene on nosocomial infections rates decreases their motivation to comply with recommendations.…”
Section: Compliance W I T H H a N D H Y G I E N Ementioning
confidence: 99%
“…27 The most effective strategy documented so far has been routine observation and feedback. 18,24,37 In 1998, Kretzer and Larson 28 revisited the major behavioral theories and their applications with regard to the health professions in an attempt to understand better how one might plan more successful interventions. They proposed a hypothetical framework to enhance hand-hygiene practices and stressed the importance of considering the complexity of individual and institutional factors when designing behavioral interventions.…”
Section: Improving Compliance With Hand Hygienementioning
confidence: 99%
“…Reported reasons for not cleaning hands include skin irritation, inaccessible hand sanitation supplies, wearing gloves, being too busy, or not thinking about it. However, people commonly believe they cleaned their hands when necessary even when observations indicated otherwise (Dubbert, Dolce, Richter, Miller, & Chapman, 1990).…”
Section: Fundamental Concepts Underlying Hand Sanitation Practicesmentioning
confidence: 99%
“…60,140,215,216,334,335,485,486,492,493,496,497,613,633,637,[648][649][650][651]654,655,657, It should be pointed out that the methods for defining adherence (or non-adherence) and the methods for conducting observations varied considerably in the reported studies, and many articles did not include detailed information about the methods and criteria used. Some studies assessed compliance with hand hygiene concerning the same patient, 60,334,648,652,666,667,683,[685][686][687] and an increasing number have recently evaluated hand hygiene compliance after contact with the patient environment. A number of investigators reported improved adherence after implementing various interventions, but most studies had short follow-up periods and did not establish if improvements were of long duration.…”
Section: Observed Adherence To Hand Cleansingmentioning
confidence: 99%